2011
DOI: 10.1099/mic.0.045567-0
|View full text |Cite
|
Sign up to set email alerts
|

Sulphite : cytochrome c oxidoreductase deficiency in Campylobacter jejuni reduces motility, host cell adherence and invasion

Abstract: Campylobacter jejuni lacks the enzyme phosphofructokinase and, consequently, is incapable of metabolizing glucose. Instead, the pathogen uses a number of other chemicals to serve as electron donors. Like chemolithotrophic bacteria, C. jejuni is able to respire sulphite in the presence of a sulphite : cytochrome c oxidoreductase (SOR) that is encoded by the genes cj0004c and cj0005c; the former encodes a monohaem cytochrome c oxidoreductase and the latter a molybdopterin oxidoreductase. After screening of a tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…Additionally, the sulfite oxidase SorA controlled by Cj1000 is also required for an efficient infection of intestinal epithelial cells by C. jejuni (Tareen et al, 2011). In this study, we showed that the O 2 consumption in the presence of sulfite as electron donors is reduced in the cj1000 mutant compared to wild-type and complemented mutant.…”
Section: Resultssupporting
confidence: 48%
See 1 more Smart Citation
“…Additionally, the sulfite oxidase SorA controlled by Cj1000 is also required for an efficient infection of intestinal epithelial cells by C. jejuni (Tareen et al, 2011). In this study, we showed that the O 2 consumption in the presence of sulfite as electron donors is reduced in the cj1000 mutant compared to wild-type and complemented mutant.…”
Section: Resultssupporting
confidence: 48%
“…jejuni also possesses multiple systems to fuel the respiratory chains with electrons, being able to utilize succinate, malate, formate, D-lactate, hydrogen and NADP(H) as electron donors (Hoffman & Goodman, 1982;Parkhill et al, 2000;Sellars et al, 2002). The hydABC operon encodes the Ni/Fe hydrogenase that catalyses the reversible oxidation of hydrogen gas (H 2 ); sorA (cj0005c) encodes a molybdopterine oxidoreductase, which along with Cj0004c (SorB), is a sulfite/ cytochrome c oxidoreductase (SOR) involved in the transformation of sulfite into sulfate and the release of electrons (Myers & Kelly, 2005;Tareen et al, 2011). The downregulation of these genes in the cj1000 : : aph mutant indicates that Cj1000 activates directly or indirectly several pathways involved in electron generation for respiration.…”
Section: Energy Metabolismmentioning
confidence: 99%
“…As with colonization, work investigating fundamental aspects of C. jejuni physiology and stress survival has also revealed roles for these properties in invasion and/or intracellular survival. Examples of factors modulating both fundamental properties and affecting host cell interactions include SorA, a sulfite-cytochrome c oxidoreductase that allows C. jejuni to use sulfite as an electron donor (51,75); AspA and AspB catalyzing fumarate production (53); Cj0952c, which affects chemotaxis toward formic acid (74); PaqPQ, involved in amino acid uptake (42); FeoB, which is important for ferrous iron acquisition (52); and SodB, required for detoxification of reactive oxygen intermediates (53,60). Mutants in several global regulators modulating aspects of physiology and/or stress survival also exhibit invasion and/or intracellular survival defects.…”
mentioning
confidence: 99%
“…The resulting PCR product with a length of 3752 bp comprised of the complete cloning vector pBluescript, the 413 5′-terminal nucleotides and the 378 3′-terminal nucleotides of cj0268c . After gel extraction of the PCR product using the QIAquick PCR Purification Kit (Qiagen), a phosphorylated blunt end kanamycin resistance cassette described previously [21] was ligated with the obtained PCR product using Quick Ligase (New England Biolabs) following the instructions of the manufacturer to obtain plasmid pBcj0268c-kanR.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to these proteins described to be involved in the process of adherence, also lipooligosaccharides (LOS) are important for pathogen-host cell interactions given that C. jejuni strains deficient in genes involved in LOS metabolism ( wlaRG, wlaTB and wlaTC ) exhibited diminished adherence properties to chicken embryo fibroblasts [20]. Recently, our group generated a C. jejuni mutant deficient in sulphite:cytochrome c oxidoreductase (SOR) which exhibited a down-regulated transcription of genes involved legionaminic acid synthesis and possessed reduced adherence properties to Caco2 cells [21]. Finally, a recently identified C. jejuni type VI secretion system (T6SS) was shown to be involved in cell adhesion.…”
Section: Introductionmentioning
confidence: 99%